Use of last generation electronic device for the experimental computation of the convection coefficient over a flat aluminum plate - Ramírez González, Luis Diego (2020)
This article deals with a jet of air at a lower temperature than the environment, which dischargesonto a flat aluminum plate located over a matrix of sensors that measures the temperature in thearea of impact. Subsequently, characteristic curves are found for each height and diameter ratioof the jet (H/D), through data processing. The coefficient of convection is determined using therelationship between the slope of the graph together with the result from the temporal evolutionof the temperature.The main objective of the work is the verification of the functionality of the advanced electronicdevice, which is carried out successfully. Also, and using visualization techniques the behaviorof the jet is analyzed. Both the electronic device and the use of air jets have great interest inthe industry (refrigeration, heating, drying processes, cleaning among others). In the case ofthe advance electronic device it is possible to provide data regarding real-time temperaturemeasurement in areas of difficult access.